2003
DOI: 10.1093/jn/133.12.4178
|View full text |Cite
|
Sign up to set email alerts
|

Anthocyanins Are Efficiently Absorbed from the Stomach in Anesthetized Rats

Abstract: After consumption, anthocyanins are rapidly absorbed as glycosides. Their rapid appearance in plasma could result from absorption through the gastric wall. The aim of this study was to evaluate the fate of anthocyanins in the stomach. Absorption of purified anthocyanins (14 micromol/L) as well as blackberry 14 and 750 micromol/L) and bilberry (88 micromol/L) anthocyanins was compared after in situ gastric administration for 30 min. A high proportion (approximately 25%) of anthocyanin monoglycosides (glucoside … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
185
1
7

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 254 publications
(214 citation statements)
references
References 28 publications
21
185
1
7
Order By: Relevance
“…In view of a possible development of new compounds as drugs, it is quite important to test antioxidant activity at acidic pH value near to that of gastric fluids. There are, in fact, several evidences that the stomach acts as a bioreactor in which many drugs can interact [22]; moreover, recent in vivo studies demonstrated that polyphenols are promptly absorbed in the stomach [23]. TEAC Measurements are conducted at pH 7.4, the physiological pH of blood, for comparison with the antioxidant activity on cells.…”
mentioning
confidence: 99%
“…In view of a possible development of new compounds as drugs, it is quite important to test antioxidant activity at acidic pH value near to that of gastric fluids. There are, in fact, several evidences that the stomach acts as a bioreactor in which many drugs can interact [22]; moreover, recent in vivo studies demonstrated that polyphenols are promptly absorbed in the stomach [23]. TEAC Measurements are conducted at pH 7.4, the physiological pH of blood, for comparison with the antioxidant activity on cells.…”
mentioning
confidence: 99%
“…Estos hallazgos se complementan bien con la buena tasa de absorción y biodisponibilidad tanto en ratas como en humanos, que tienen las antocianinas presentes en el Zea mays L (25)(26)(27) ; en especial la cianidina 3 glicósido, la cual, tras ser administrada por vía oral, es incorporada a la circulación manteniendo su estructura química intacta (27) . A pesar de ello, es necesario recalcar que los resultados obtenidos no pueden extrapolarse en su totalidad al ser humano o reemplazar la terapia medicamentosa actual de la hipertensión.…”
Section: Discussionunclassified
“…Previous in vivo studies have reported that anthocyanins are absorbed in the stomach and small intestine (Passamonti et al, 2003a;Talavera et al, 2003;Talavera et al, 2004). Felgines and colleagues administered an oral dose of a radiolabelled cyanidin 3-O-glucoside, demonstrating that the major site of absorption in mice is the intestine with a minimal accumulation of the radioactivity in tissues out of the gastrointestinal tract (Felgines et al, 2010).…”
Section: Membrane Transport Of Anthocyaninsmentioning
confidence: 99%